Pengaruh Budaya Organisasi terhadap Kesejahteraan Karyawan di Kawasan Industri Purwakarta, Subang, dan Karawang: Indonesia - Casiman, Casiman; Ramadhan, Noval Dwi Sanggar; Sugiantoro, Wahyu; Sofyan, Hady (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
Employee well-being in industrial areas is often neglected amidst tight production targets, leading to work stress and high turnover rates. This study aims to analyze the simultaneous influence of organizational culture dimensions on holistic employee well-being. The research method uses a quantitative approach with multivariate Structural Equation Modeling (SEM) analysis on 99 respondents in the industrial areas of Purwakarta, Subang, and Karawang. The results show that organizational behavior has the strongest significant positive influence on psychological well-being (p=0.001). In addition, organizational norms significantly affect social and economic well-being (p=0.019), while psychological well-being is the main determinant of social-economic well-being. This model shows a very strong predictive power with an R² value > 0.87. In conclusion, strengthening organizational culture through positive behavior and fair norms is crucial to improve employee well-being sustainably